High prevalence of rectal chlamydia among pregnant adolescents in La Romana, Dominican Republic warrants extragenital STI testing. (January 2022) - Bancalari, Pilar; Nicholas, Catherine; Halpern, Mina; Stonbraker, Samantha; Taylor, Barbara; Soriano, Leidy; Ljubicic, Dana; Amesty, Silvia
To our knowledge, there are no studies estimating the prevalence of extragenital sexually transmitted infections (STIs) among pregnant adolescents in the Caribbean. This study sought to fill this gap by assessing the prevalence and correlates of oral, genital, and rectal chlamydia (CT) among a sample of pregnant adolescents in La Romana, Dominican Republic. Two hundred pregnant youths, aged 15–24 years, were recruited by systematic sampling during their first prenatal visit to a maternal care unit. A sociodemographic and behavioral questionnaire was administered and urine and oral/anal swabs were collected and tested for CT. Descriptive analyses and Fisher's exact tests were performed. The prevalence of oral, genital, and rectal CT was 6%, 15%, and 23%, respectively, although less than 5% of participants reported ever engaging in receptive anal intercourse. This discrepancy could be explained by autoinoculation, concurrent transmission during sex, undertreatment of rectal CT, or underreporting of anal sex. Almost half of CT infections would have been missed if only genital samples were collected, as current protocol dictates. More research is needed to understand sexual behaviors and rectal STI risk factors among heterosexual adolescent women. STI screening procedures for pregnant and sexually active adolescents should include routine testing of extragenital sites.